Age-Associated Gut Dysbiosis, Marked by Loss of Butyrogenic Potential, Correlates With Altered Plasma Tryptophan Metabolites in Older People Living With HIV. (1st February 2022) - Ghare, Smita; Singhal, Richa; Bryant, Vaughn; Gautam, Sabina; Tirumala, Chanakya Charan; Srisailam, Praneet Kumar; Reyes-Vega, Andrea; Ghooray, Dushan; McClain, Craig J.; Hoffman, Kristi; Petrosino, Joseph; Bryant, Kendall; et al.
Abstract : Background: Imbalance in tryptophan (TRP) metabolism and its neuroactive metabolites, serotonin and kynurenine (KYN), is a known pathogenic mechanism underlying neurocognitive impairment. Gut microbiota plays an important role in TRP metabolism, and the production of these neuroactive molecules affects neurocognitive function. Although both HIV infection and normal aging independently induce gut dysbiosis and influence TRP metabolism, their interactive effects on compositional/functional changes in gut microbiota and consequent alterations in TRP metabolites remain largely undetermined. Methods: Older people living with HIV infection (PLWH, aged 50–70 years, n = 22) were enrolled in this cross-sectional pilot study. Metagenomic analysis of fecal microbiome using 16S Ribosomal ribonucleic acid gene sequencing and metabolomics analysis of plasma using mass spectrometry with a reverse-phase iquid chromatography tandem mass spectrometry were performed. Statistical analyses included the univariate linear regression and Spearman correlation analyses. Results: Age-associated changes in plasma levels of key neuroactive TRP metabolites, serotonin and KYN, were seen in PLWH. Specifically, we observed age-dependent decreases in serotonin and increases in KYN and KYN-to-TRP ratio, indicative of dysfunctional TRP metabolism. Furthermore, the gut dysbiosis seen in older PLWH is characterized by a reduction of Firmicutes/Bacteroidetes ratio and butyrate-producing microbial families Lachnospiraceae and Lactobacillaceae. Of importance, correspondent with gut dysbiosis, increasing age was significantly associated with decreased plasma butyrate levels, which in turn correlated positively with serotonin and negatively with KYN/TRP ratio. Conclusions: Age-dependent gut microbial dysbiosis distinguished by a decrease in butyrogenic potential is a key pathogenic feature associated with the shift in TRP metabolism from serotonin to KYN in older PLWH.